HUBUNGAN SELF COMPASSION TERHADAP PERILAKU CERDIK DAN PATUH PADA PASIEN PASCA STROKE DALAM MENCEGAH STROKE BERULANG DI WILAYAH PUSKESMAS KECAMATAN GROGOL PETAMBURAN, JAKARTA BARAT - Srimpi Pamulatsih, (2022)
Stroke is a medical term to describe neurological changes due to disruption of blood supply to the brain. One of the factors that cause more severe disability and even death in post-stroke patients is redurrent stroke. Efforts that's post-stroke patients can do are by doing CERDIK and PATUH behaviors wich is a government program through the Gerakan Masyarakat Sehat to prevent and exacerbate non-communicable diseases, in reaserch to prevent recurrent strokes. There are many obstacles to comply with CERDIK and PATUH behaviors, one of wich is the lack of self-awareness to do self-improvement duringthe rehabilitation by accepting their illness so that they feel compassion for themselves. This study aimed to determine the relationship between self-compassion and CERDIK and PATUH behaviors in stroke patiens in preventing recurrent stroke in the Puskesmas area Grogol Petamburan District. This research is a quantitative study with a cross-sectional approach and was conducted on 101 respondents using the purposive sampling method. Data collectiion is using two questionnaries. CERDIK and PATUH behaviors of post-stroke patients are in a good category. CERDIK and PATUH behaviors was not influenced by age (p = 0.196), length of stroke (p = 0,757), and gender (p = 0,273). However, it was influenced by education (p = 0,00) and self-compassion (p = 0,00). Keywords: self-compassion, CERDIK and PATUH behaviors, post-stroke, recurrent stroke